P219 Quantifying heat stress and strain in summer tree fruit harvesters in yakima valley, washington. (1st September 2016) - Quiller, Grant; Spector, June; Krenz, Jennifer; Calkins, Miriam; Palmández, Pablo; Negrete, Maria; Carmona, Jose
Abstract : Outdoor workers performing heavy physical labour in hot conditions are at increased risk for developing occupational heat-related illness. Seasonal harvesting of certain tree fruits in Washington occurs during summer months. In addition to environmental heat exposure, harvesting involves internal heat generation from physical work. We sought to characterise heat stress and physiological effects of heat stress (heat strain) in workers performing harvest activities. During the summer of 2015, 46 pear and apple harvesters participated in a cross-sectional study in Yakima Valley, Washington for one work shift during warmer periods in August (n = 34) and cooler periods in September (n = 12). Heat stress and strain were characterised using American Conference of Governmental Hygienist (ACGIH) guidelines, which recommend thermal Action Limits and Threshold Limit Values based on several factors including: environmental temperatures, metabolic rate of task, clothing ensembles, core body temperature, and heart rate. Heat exposure was measured near individual workers using hand-held Wet Bulb Globe Temperature (WBGT) monitors, metabolic rate was estimated using field observations and hip-mounted accelerometers, and research staff observed workers' clothing. Heart rate and core body temperature were monitored using heart rate monitors and ingestible core body temperature sensors. Of the 46 participants, 25 (54.4%) exceeded the ACGIH Action Limit (WBGT 25°C), and 16 (34.8%) exceeded the Threshold Limit Value (WBGT 28°C) for a moderate work task (300 Watts). All participants exceeding the Threshold Limit Value were working in August. Using accelerometer data (n = 39), 12 (30.8%) exceeded the Action Limit and 4 (10.3%) exceeded the Threshold Limit Value. Heat strain data are currently being analysed. Under current conditions, workers are exposed to hazardous thermal environments. Future climate conditions may further impact physically intensive outdoor occupations. Effective approaches for reducing heat exposure and/or promoting biological adaptation to heat are needed to prevent heat-related illness in vulnerable working populations.